Reforma agrária no Triângulo Mineiro: memórias, histórias e lutas de assentados(as) dos Projetos de Assentamento Emiliano Zapata e 21 de abril (1980-2012) - Silvério, Leandra Domingues (2012)
THIS THESIS EXAMINES the social experiences in the struggle for agrarian reform settlers of the Settlement Project (PA) Emiliano Zapata, located in Uberlândia and created in 2004, and Settlement Project 21st April, in the city of Veríssimo and created in 2005, both in the Triângulo Mineiro region. During the process of major transformation of social relations in the Brazilian countryside in recent decades, particularly in the Triângulo Mineiro, focusing on research with oral history and interpreting a set of statements from workers of these Settlement Projects, it discusses paths, ways and meanings of their struggles for maintaining their own plots of land after the conquest. In the relationship between history and memory, it addresses issues concerning the daily challenges of living and nesting in this new territory and how these settlers organize themselves by means of values and customs acquired in previous struggles. It examines the continuity of the fight after the conquest of the land and how the rural workers give meaning to this fight revealing current perspectives and projected future as settlers. It also problematizes their practices and views on public policies for the settlers and discusses the changes of such policies in recent decades amid the transformations on the role and the importance of smallholder agriculture. The study is organized into four chapters that discusses the following topics: social and political education of both groups of settlers and of the Settlement Projects; the experiences of workers in the conquered land and their organization and practices on their daily lives; the expectations of workers regarding projects related to rural life in the pursuit of autonomy and freedom; and finally, actions and struggles of settlers to maintain the right to live on/from the land by means of being able to have access to public funding and investment policies in the agrarian reform